Evidence of Subproton‐Scale Magnetic Holes in the Venusian Magnetosheath. Issue 5 (1st March 2021) - Goodrich, Katherine A.; Bonnell, John W.; Curry, Shannon; Livi, Roberto; Whittlesey, Phyllis; Mozer, Forrest; Malaspina, David; Halekas, Jasper; McManus, Michael; Bale, Stuart; Bowen, Trevor; Case, Anthony; et al.
Abstract: Depressions in magnetic field strength, commonly referred to as magnetic holes, are observed ubiquitously in space plasmas. Subproton‐scale magnetic holes with spatial scales smaller than or on the order of a proton gyroradius, are likely supported by electron current vortices, rotating perpendicular to the ambient magnetic field. While there are numerous accounts of subproton‐scale magnetic holes within the Earth's magnetosphere, there are few, if any, reported observations in other space plasma environments. We present the first evidence of subproton‐scale magnetic holes in the Venusian magnetosheath. During Parker Solar Probe's first Venus Gravity Assist, the spacecraft crossed the planet's bow shock and subsequently observed the Venusian magnetosheath. The FIELDS instrument suite onboard the spacecraft achieved magnetic and electric field measurements of magnetic hole structures. The electric fields associated with magnetic depressions are consistent with electron current vortices with amplitudes on the order of 1  μ A/m 2 . Plain Language Summary: The Sun is constantly ejecting an ionized gas, or plasma. This plasma from the Sun is called the solar wind and usually consists of an equal number of negatively charged electrons and their larger positively charged counterparts, protons. These particles travel together from the Sun, canceling out each other's charge. When the plasma encounters obstacles, however, like the Earth or Venus, the plasma becomes disturbed. This can cause the electrons to separate from the protons and form unbalanced structures. One interesting structure that has recently been discovered at Earth are electron vortices. These vortices can create their own magnetic and electric fields and slightly alter the plasma around them. We have seen electron vortices where the solar wind meets the Earth, but are not sure how they are created or how strongly they affect the plasma around them. We report, for the first time, evidence of electron vortices where the solar wind encounters Venus. These new findings show the process that creates electron vortices takes place at both Earth and Venus, strongly implying a universal process in space. Key Points: Magnetic depressions with spatial scales less than the local proton gyroradius are observed in the Venusian magnetosheath The amplitude and features of the electric field associated with these structures are consistent with electron vortices, though they deviate in direction by 90° Similar structures have been observed in the terrestrial magnetosphere, suggesting they are part of a universal plasma process